EVALUASI KEMAMPUAN LAHAN REKLAMASI PASCA TAMBANG DI KECAMATAN MERAPI BARAT KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - Muhammad Fajri Azhari; Iswandi Umar (Universitas Negeri Padang, 2021)
The purpose of this research is to find out how the capability class of post-mining reclamation land in West Merapi Subdistrict, Lahat Regency, South Sumatra Province. As well as how the direction of land use is in accordance with the capacity of the land from post-mining reclamation in West Merapi District, Lahat Regency, South Sumatra Province. This research uses quantitative descriptive exploratory research method, the research sample is obtained from laboratory tests and direct measurements. Research results The land capability in the reclamation area in 2019 is included in the class III land capability class with an area of ​​the post-mining land reclamation area of 5.4 Ha or 54,775 m ^ 2. Directions Land use Class III is suitable for all types of agricultural business with special soil preservation measures such as terracing, crop rotation, and groove planting systems, to maintain soil fertility such as fertilization. The land capability in the 2020 reclamation area is included in the Class IV land capability class with a post-mining land reclamation area of 11.09 hectares or 111,905 m ^ 2. Class IV soil itself is still classified as fertile soil and is still suitable for agricultural business with a more specific and heavier level of soil preservation so that the land with this Class IV land capability classification can be utilized optimally.